Perlindungan Hukum Ahli Waris Dibawah Umur Terhadap Penjualan Tanah Harta Waris Yang Dilakukan Oleh Wali (Studi Kasus Putusan Nomor: 313/Pdt.P/2023/PN Dps) - K, Klamajaya; Hakim, Luqman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this research is to analyze and answer what is the legal protection of underage heirs against the sale of inherited property by the guardian. The research method used is legal research with a normative juridical approach. The results of this study indicate that the form of legal protection of underage heirs against the sale of inherited property land carried out by guardians Minors cannot transfer land rights alone because there is no legal capacity possessed by children as legal subjects in legal actions. Therefore, the transfer of land rights must be carried out by someone who represents the minor, whether it is a parent or guardian appointed in accordance with applicable legal provisions. The aim is to prevent possible claims or lawsuits from other parties regarding the validity of land ownership by the new right holder.